Investigation of lightning damages in glass fibre-reinforced prepreg composites - Gan, Chia Sheng (2019)
Glass fibre reinforced polymers (GFRP) are typically used in aircraft parts where lightning strikes the most. Recent studies had been focusing on lightning damage on carbon fibre reinforced polymers (CFRP) instead of GFRP. Besides that, the main nondestructive evaluation (NDE) technique used to detect lightning damage in these studies is water immersion ultrasonic c-scan instead of Ultrasound Propagation Imaging (UPI). Thus, it can be seen that the detection and evaluation of lightning damages on GFRP using UPI is not well investigated. This study aims to accurately and statistically detect, define the shape and size, and evaluate the severity of lightning damages in GFRP using UPI. Four 1-layer and two 3-layer GFRP specimens had been manufactured and struck using various breakdown voltages, which are 6kV, 7kV, and 16kV 1.2/50µs impulse voltages, for three of the 1-layer specimens respectively, and 18kV 1.2/50µs impulse voltage for the rest of the specimens. The lightning simulation standards used in this study are IEC 60060-1 (2010), IEC 60060-2 (2010), and IEC 60060- 3 (2006). Ultrasonic data were obtained using a UPI system and were subsequently processed using the Statistically Thresholded Anomaly Mapping (STAM) technique that was developed in this study. The results show that the damage size increases proportionally with the increase of breakdown voltage, which are 27.75mm2, 29.72mm2, and 38.5mm2 for 6kV, 7kV and 16kV breakdown voltages respectively for the 1-layer specimens. A significant increase in damage size (847.25mm2) was detected on Specimen 4 due to an unexpected surface flashover event. 3-layer specimens suffered greater damages, measuring 597.25mm2 and 573.5mm2 respectively, compared to 1- layer specimens due to 3-layer specimens being susceptible to delaminations. The results proved that lightning damage in GFRP could be detected using the UPI system. The STAM technique developed in this project could distinct damage from the noise based on a statistical threshold, hence could provide higher reliability and accuracy in evaluating the size of lightning damage. Lastly, it was found that the size of lightning damages increases when breakdown voltage increases, subjected to further investigations.